Organizational Justice and Turnover Intention: The Mediation Role of Job Satisfaction (Global Business Management Review (GBMR), 2022)
This research examines the relationship between the facets of organizational justice namely; distributive justice and procedural justice on turnover intention and determining the mediating role of job satisfaction among IT professionals. The social exchange theory is reviewed in this paper as the theoretical perspectives which guide the development of hypotheses. 550 IT professionals were sampled and survey from the ICT industry in Thailand. Using both SPSS and AMOS packages, the collected data was analyzed using a multivariate technique. This study found a statistically significant relationship between distributive justice, procedural justice and employee turnover intention through the mediating effect of job satisfaction of IT professionals in Thailand. The findings of this study offer a constructive contribution to the understanding of psychological processes of job satisfaction using the paradigm of social exchange theorists (Blau, 1964). The implications of the findings are discussed in details in the study and constructive recommendations are proffered for future researchers.